The role of ubiquitylation in regulating apurinic/apyrimidinic endonuclease 1 - Meisenberg, C (2012)
Apurinic/apyrimidinic endonuclease 1 (APE1) is a key DNA repair factor involved in the DNA base excision repair (BER) pathway that is required for the maintenance of genome stability. In this pathway, APE1 cleaves DNA at an abasic site to generate a DNA single strand break, allowing for repair completion by a DNA polymerase and a DNA ligase. High levels of APE1 have been observed in multiple cancer types however it is not understood if this contributes to cancer onset and development. What is known is that these cancers tend to display increased resistance to DNA damaging treatments and APE1 is therefore considered a key target for inhibition in the treatment of APE1-overexpressing cancers. Considering the relevance of modulating APE1 levels in disease and cancer treatment, very little is known about how cellular APE1 levels are regulated. Our lab has previously shown that the levels of the BER factors Pol β, XRCC1 and DNA Lig IIIα are regulated by ubiquitylation-mediated proteasomal degradation. The aim of this doctoral thesis was therefore to determine if ubiquitylation also regulates APE1 stability in cells. I present evidence that APE1 is ubiquitylated in cells and have identified the UBR3 E3 ligase that is responsible for this activity. Using mouse embryonic fibroblasts generated from Ubr3 knockout mice, I demonstrate that UBR3 regulates APE1 cellular levels. I furthermore show that a loss of cellular UBR3 leads to the formation of DNA double strand breaks and genome instability.